Combined Toxoplasma gondii seropositivity and high blood kynurenine – Linked with nonfatal suicidal self-directed violence in patients with schizophrenia. (January 2016) - Okusaga, Olaoluwa; Duncan, Erica; Langenberg, Patricia; Brundin, Lena; Fuchs, Dietmar; Groer, Maureen W.; Giegling, Ina; Stearns-Yoder, Kelly A.; Hartmann, Annette M.; Konte, Bettina; Friedl, Marion; Brenner, Lisa A.; et al.
Abstract: Toxoplasma gondii (T. gondii ) chronic infection and elevated kynurenine (KYN) levels have been individually associated with non-fatal suicidal self-directed violence (NF-SSDV). We aimed to test the hypothesis that the association between T. gondii seropositivity and history of NF-SSDV would be stronger in schizophrenia patients with high plasma KYN levels than in those with lower KYN levels. We measured anti- T. gondii IgG antibodies and plasma KYN in 950 patients with schizophrenia, and used logistic regression to evaluate the relationship between NF-SSDV and KYN in patients who were either seropositive or seronegative for T. gondii . For those with KYN levels in the upper 25th percentile, the unadjusted odds ratio for the association between NF-SSDV history and KYN in T. gondii seropositive patients was 1.63 (95% CI 1.01 to 2.66), p  = 0.048; the adjusted odds ratio was 1.95 (95% CI 1.15 to 3.30), p  = 0.014. Plasma KYN was not associated with a history of NF-SSDV in T. gondii seronegative patients. The results suggest that T. gondii and KYN may have a nonlinear cumulative effect on the risk of NF-SSDV among those with schizophrenia. If confirmed by future longitudinal studies, this result is expected to have both theoretical and clinical implications for the prevention and treatment of suicidal behavior. Highlights: We studied interactions among Toxoplasma gondii seropositivity, plasma kynurenine, history of suicide attempts, and schizophrenia. Elevated kynurenine was associated with history of NF-SSDV only in schizophrenia patients seropositive for T. gondii . T. gondii and KYN may have a nonlinear cumulative effect on the risk of NF-SSDV in patients with schizophrenia.